First tergal structures for the fossil stonefly genus Largusoperla (Plecoptera: Perlidae): a new species and a new tribe of Acroneuriinae - Chen, Zhi-Teng (Zootaxa, 2018)
Based on a well-preserved adult male specimen from mid-Cretaceous Burmese amber, a new species of the fossil stonefly genus Largusoperla Chen et al. 2018, L. crassus sp. nov. is described. The male holotype exhibits asymmetrical paraprocts and conspicuous tergal characters, previously unknown for the genus. A new tribe of Acroneuriinae, Largusoperlini trib. nov. is proposed for this male adult based on the presence of these newly observed tergal characters.